Influence of selected production parameters on the hand of mattress knitted fabrics assessed by the Fabric Touch Tester. Issue 1 (January 2019) - Vasile, Simona; Malengier, Benny; De Raeve, Alexandra; Deruyck, Frank
The overall comfort of a bedding system is, among others, the result of the moisture and thermal management capabilities of its components, including mattress ticking fabrics. The hand of mattress ticking fabrics, their smoothness, softness, flexibility, and thermal properties, in particular, partially contribute to the sleep quality. Manufacturers pay a great deal of attention to this aspect and make efforts to improve fabric hand as customers always touch and squeeze the fabric and the perceived fabric hand will partially influence their buying decision. In this study the hand of 12 mattress fabrics was investigated by the Fabric Touch Tester (FTT), which is a relatively new characterization method of fabric hand. The FTT measures simultaneously 13 fabric indices related to four categories of fabric physical properties, namely bending, compression, and thermal and surface properties. These fabric indices are subsequently used by the FTT software to predict three primary comfort indices (i.e. smoothness, softness, warmth) and two global comfort indices (i.e. total hand and total feel). The fabrics were differentiated by three production parameters, namely fabric mass per unit area, concentration of softener and fiber composition. Relevant tactile properties for mattress ticking fabrics, such as smoothness, softness, warmth, and flexibility, were assessed by an expert panel and the average scores given by the assessors were correlated with the fabric indices measured by the FTT. Among the selected variables, fabric mass per unit area has the greatest influence on all FTT fabric indices. Due to the large fabric set, considerable variances were observed between the scores assigned by the panels. That resulted in poor correlations between tactile properties and selected production parameters, although the trend seems to be correct and all the factors were found to be statistically significant. Strong correlations were found between the FTT fabric indices and tactile properties assessed by the panels, except warmth, which suggests that the FTT is suitable to assess mattress ticking fabrics with elevated mass per unit area and uneven texture.